The role of seed vouchers and fairs in promoting seed market development: Opportunities and limitations - Croft, Marcia M.; Davis, Valerie; Longley, Kate; Ferris, Shaun; Templer, Noel (2021)
This review aims to identify whether the seed voucher and SVF/DiNER model can be modified over time (e.g., 2-5 years) to build capacity within the seed sector to support the emergence of a sustainable, market-based seed system that offers quality, affordable seeds to smallholder male and female farmers. This scoping report presents a review of the wide variety of approaches that have been tested or recommended across International NGOs. These include both adjustments to the seed voucher and SVF/DiNER model itself as well as additional activities implemented alongside or in place of SVF/DiNER fairs to address market constraints and promote the emergence of alternative viable seed markets.